Development of a preschool creative play early science module / Tee Ying Qin - Tee, Ying Qin (2018)
Creativity is a crucial 21st century skill which should be developed among young children from an early age. However, this essential skill has not been sufficiently and effectively infused at the preschool level in Malaysia, where preschoolers are at the golden age of learning and development. Therefore, this study developed a preschool Creative Play Early Science (CREPES) module. This module aims to provide pedagogical support for preschool teachers in teaching early science through creative play activities, hence developing preschoolers’ creativity. Based on the design and development research (DDR) approach (Richey & Klein, 2007), the study was structured into three phases. The first phase analysed the contextual needs in preschool science teaching and learning in Malaysian private preschools. Qualitative data were collected via interviews and observations. Findings for this phase illustrated and ascertained the need for the development of a creative play science module. In the second phase, the CREPES module was designed and developed. This was achieved through employing a three-round Delphi with a panel of 14 experts. Consensus of the panel experts resulted in 57 items on five aspects including general module design, recommended module sections, module activities, teaching strategies or techniques, and module resources. Based on these items, an initial module was produced and subsequently reviewed by three content experts and two preschool teachers. Appropriate amendments to the initial module were made based on reviewers’ comments. Following the review, a module prototype was developed. The last phase of the study involved the implementation and evaluation of the CREPES module. Six module activities were implemented in a preschool setting in Klang Valley by two teachers with 29 preschoolers over three weeks. Prior to the implementation, a module orientation session was held to train teachers in implementing the module effectively. To determine the usability of the module for teachers and preschoolers, observations and interviews with teachers were conducted. In addition, impact of the CREPES module on preschoolers’ creativity was measured in a quasi-experiment. Torrance’s Thinking Creatively in Action and Movement (TCAM) was administered individually to preschoolers before and after the module intervention. Findings of ANCOVA revealed that after controlling for the effect of pretest, the overall creativity scores of preschoolers from experimental and control groups differed significantly, F(1,53) = 5.23, p = 0.03, partial eta² = 0.09. Preschoolers in the experimental group who had participated in the CREPES module activities were found to score significantly higher in their average TCAM posttest score compared to the control group. This reinforces the positive impact of the CREPES module in significantly enhancing preschoolers’ creativity, specifically in terms of originality and imagination. This research study demonstrated that the CREPES module effectively helped teachers in incorporating creativity in preschool science instruction. A proposed creative play framework was also postulated to promote the implementation of creative play in developing creativity among preschoolers. Development of other pedagogical tools for preschool education should be vigorously continued in future research studies for the benefit of preschoolers in Malaysia.